Preparation of Dicalcium Phosphate Anhydrous (Monetite) Biological Coating on Titanium by Spray-Drying Method - Xingling Shi; Chao Zhao; Lingli Xu; Qingliang Wang (Advances in Materials Science and Engineering)
Titanium and its alloys have been widely used in the manufacture of endosseous implants due to excellent biocompatibility, low elastic modulus, and good chemical stability. However, the titanium based metals are essentially bioinert materials. In order to improve their bioactivity, biological coatings are usually applied. Recent studies found that, compared with hydroxyapatite coating, dicalcium phosphate anhydrous (DCPA, Monetite) coating maybe more bioactive due to higher solubility and release of Ca and P ions. In this work, DCPA coating was prepared through a novel and simple method. Briefly, high concentration DCPA solution was sprayed onto superhydrophilic titanium and the specimens were dried fast in an air-circulating oven. After repeating the process over 100 times, a compact coating was fabricated. The microstructure, chemical composition, wettability, and in vitro bioactivity of the coating were analyzed and evaluated. Results showed that the coating fully covered the substrate and consisted of a large number of uniformly sized DCPA granules that packed together closely. The coating showed good wettability and could keep the property for a long time. After immersion in simulated body fluid for 2 weeks, a large amount of bone-like apatite with low crystallinity was induced implying a good bioactivity.